Shifting towards Urban Electronic Governance using Artificial Intelligence: A Legal Analysis of Challenges and Opportunities - GHUNEMAT, HAMDN; Mahdi, Musaab Faraj; Arabiyyat, Abdullah Radwan (Journal of Ecohumanism, 2024)
There is a rapid spread of artificial intelligence applications (AIA hereafter) worldwide resulting in their intervention in various fields, yet electronic management is not exceptional. This study illustrated the role of AIAs in the electronic management of public facilities in the government sector. In order to obtain rich data, the researcher employed a descriptive, analytical, and legal interpretive methodology. The main result showed that the administrative staff had a limited ability to deal with modern technology. It also indicated that AIAs might be used within open-source software or social networks to infringe upon the privacy of individuals and institutions.